Emergency and delayed microsurgical salvage of traumatic lower extremities: Reconstruction of lower extremity injuries - Gur, Ersin; Tiftikcioglu, Yigit Ozer; Kuybulu, Turgut Furkan; Durukan, Kutay; Yegin, Mehmet Emre; Ozkayin, Nadir (Journal of Surgery and Medicine, 2023)
Background/Aim: The power of free flaps for lower extremity injury reconstruction is no longer a matter of debate; however, contrasting views remain regarding the timing of reconstruction. The mainstay article of Godina reported that reconstruction within the first three days after injury was more advantageous than surgery at later times, but different views about the best day for reconstruction have also been described in the literature. With developments in the field of microsurgery, plastic surgeons have become more experienced, shortened the times needed for surgery, and achieved flap success. We have also become more experienced with surgical times, and reconstruction on the day of injury has been performed as an emergency reconstruction (ER) procedure since 2018. However, despite the disadvantages of a delayed wait period, patients still experience delayed reconstruction (DR) due to their pre-operative conditions and dispatches from peripheral centers over delayed time periods. This study aimed to present our experiences with lower extremity reconstruction in emergency situations and after delayed periods with descriptions of technical tips for each situation. Methods: Between 2018 and 2021, patients who underwent lower extremity reconstructions were examined as retrospective case-control study. Twenty-four patients (17 male and seven female) underwent lower extremity reconstructions with microsurgical free flap coverage. Patients’ ages ranged from 6 to 75 years old. Ten patients underwent ERs (on the day of injury), and 14 patients underwent DRs. Twenty anterolateral thigh, two medial sural artery perforator, one latissimus dorsi, and one radial forearm flaps were chosen for reconstructions. Flaps were chosen for one-third of the distal lower extremity reconstructions (n=11) and Gustilo type 3B injuries (n=11), Gustilo type 3C injuries (n=1), and one-third for middle lower extremity soft tissue reconstructions (n=1). Infections, length of hospital stays, time spent during the reconstructive surgery, vascular complications, and additional debridement necessity counts were recorded and compared with previous statistical analyses. Results: One venous thrombosis in the emergency group and three venous and one arterial thrombosis in the delayed group were reported. The patients were taken to the operating room immediately after which re-anastomoses were performed successfully, and all flaps survived. The hospital stay was between 4 and 60 days in the emergency group and 20 and 99 days in delayed group. Infections (P=0.03), vascular complications (P=0.04), and hospital stays (P=0.01) were statistically significantly lower in the emergency group than in the delayed group. Conclusion: ER has many advantages, such as preventing time consuming surgeries and providing short hospital stays and low complication rates, over DR. However, DR is inevitable for some reasons, and despite its more complicated nature, meticulous flap follow-up and salvage procedures may provide the same flap success as found with ERs.